Rural Redemption: A Model to Help Understand the Perspectives of Rural Americans Related to Vaccine Science - Lauri Baker; Ashley McLeod-Morin; Chen-Xian Yang; Audrey E. H. King; Shelby Thomas; Kristina Boone (Journal of Applied Communications, 2023)
Rural communities are vital to the foundation of American agriculture and are currently disproportionately affected by health and environmental challenges that will require broad scientific solutions. Cooperative Extension professionals and agricultural communicators are increasingly tasked with communicating about the science surrounding these topics and need effective tools for determining strategic communication tactics to influence personal behaviors. The purpose of this study was to understand the role of community-based social marketing (CBSM) concepts and trust in science on rural Americans’ intentions and attitudes toward the COVID-19 vaccine. A hypothesized model was developed that included concepts of CBSM, trust in science, intentions, and attitudes all related to the COVID-19 vaccine. Results showed that CBSM principles had significant explanatory power for predicting intentions to receive the COVID-19 vaccine. CBSM and trust in science were also significant predictors of rural Americans attitudes toward the COVID-19 vaccine. Implications for this study reveal a need for future research and practice related to communicating about science and vaccines to rural Americans while building community-based principles for increasing trust and advancing perceptions of science. Future research should determine the impact of CBSM and trust in science on the end-state behavior of receiving the vaccine. Additionally, Extension professionals and agricultural communicators should prioritize CBSM concepts when developing programming and messages related to health behaviors.
Keywords: trust in science; community-based social marketing; rural communities; risk communication; public opinion